Biallelic variants in ZNF142 lead to a syndromic neurodevelopmental disorder. Issue 2 (8th June 2022) - Christensen, Maria B.; Levy, Amanda M.; Mohammadi, Nazanin A.; Niceta, Marcello; Kaiyrzhanov, Rauan; Dentici, Maria Lisa; Al Alam, Chadi; Alesi, Viola; Benoit, Valérie; Bhatia, Kailash P.; Bierhals, Tatjana; Boßelmann, Christian M.; et al.
Abstract: Biallelic variants of the gene encoding for the zinc‐finger protein 142 ( ZNF142 ) have recently been associated with intellectual disability (ID), speech impairment, seizures, and movement disorders in nine individuals from five families. In this study, we obtained phenotype and genotype information of 26 further individuals from 16 families. Among the 27 different ZNF142 variants identified in the total of 35 individuals only four were missense. Missense variants may give a milder phenotype by changing the local structure of ZF motifs as suggested by protein modeling; but this correlation should be validated in larger cohorts and pathogenicity of the missense variants should be investigated with functional studies. Clinical features of the 35 individuals suggest that biallelic ZNF142 variants lead to a syndromic neurodevelopmental disorder with mild to moderate ID, varying degrees of delay in language and gross motor development, early onset seizures, hypotonia, behavioral features, movement disorders, and facial dysmorphism. The differences in symptom frequencies observed in the unpublished individuals compared to those of published, and recognition of previously underemphasized facial features are likely to be due to the small sizes of the previous cohorts, which underlines the importance of larger cohorts for the phenotype descriptions of rare genetic disorders. Abstract : Zinc‐finger protein 142, encoded by ZNF142, belongs to a family transcriptional repressors that recruit chromatin remodeling proteins to DNA. They are widely expressed and are important for numerous processes such as development, cell differentiation and proliferation, and apoptosis. Zn 2+ ions (gray) and three modellable missense variants (yellow) are depicted as spheres.